2014
DOI: 10.21273/hortsci.49.10.1305
|View full text |Cite
|
Sign up to set email alerts
|

Flurprimidol Performance on Ornamental Species in Relation to Trimming Time and Method of Application

Abstract: The plant growth regulator flurprimidol (Cutless G) is registered for use on ornamental plants to reduce internode elongation and reduce trimming frequency. It has been hypothesized that timing of the trimming event can be related to the efficacy of the flurprimidol treatment. Granular flurprimidol was applied to well-established plants at a standard rate of 22.5 g/a.i. (15 lbs product)/1000 ft2 on 23 Apr. 2012 and 1 May 2013.Two common Florida landscaping species, Vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…To eliminate the apical dominance effect, the first internode was trimmed in this study. This was consistent with the report of Smith et al (2014), where the removal of terminal buds will stimulate water uptake and cause redistribution of carbohydrate reserves to the injured parts for healing the wounds and promoting new shoot formation. Similarly, flurprimidol, which is translocated through the xylem will also be uptaken, making it available for regulating gibberellin throughout the whole plant.…”
Section: Shoot Regenerationsupporting
confidence: 93%
“…To eliminate the apical dominance effect, the first internode was trimmed in this study. This was consistent with the report of Smith et al (2014), where the removal of terminal buds will stimulate water uptake and cause redistribution of carbohydrate reserves to the injured parts for healing the wounds and promoting new shoot formation. Similarly, flurprimidol, which is translocated through the xylem will also be uptaken, making it available for regulating gibberellin throughout the whole plant.…”
Section: Shoot Regenerationsupporting
confidence: 93%
“…Plants were monitored weekly for 8 weeks after treatment and then assigned a numerical value of 0 through 10 to describe the visual quality (0 = dead; 5 = fair quality, acceptable, somewhat desirable form and color, little to no chlorosis or necrosis; 10 = excellent quality, perfect condition, healthy and robust, excellent color and form). We recorded visual quality, which has been used to describe the plant response to differing culture conditions (Gettys andMoore, 2018, 2019;Gettys et al, 2021), herbicides ( Gettys and Haller, 2009, 2010Smith et al, 2014), salt stress (Tootoonchi et al, 2020), and other experimental factors, although some researchers (Cutelle et al, 2013;Koschnick et al, 2005;Mudge et al, 2007) have reported visual injury or damage resulting from herbicide treatments. After visual scoring, a destructive harvest was conducted to collect all live biomass of floating species and all live aboveground shoots of emergent species; harvested materials were placed in paper bags and moved to a forced-air oven maintained at 65 C for 2 weeks before being weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Plants were monitored weekly for 8 weeks after treatment and then the project lead assigned a numerical value of 0 through 10 to describe visual quality (0 = dead; 5 = fair quality, acceptable, somewhat desirable form and color, little to no chlorosis or necrosis; 10 = excellent quality, perfect condition, healthy and robust, excellent color and form). Although some authors (e.g., Cutelle et al, 2013;Koschnick et al, 2005;Mudge et al, 2007) report visual injury or damage resulting from herbicide treatments, we recorded visual quality, which has also been used to describe plant response to differing culture conditions (e.g., Gettys andMoore, 2018, 2019), herbicides (e.g., Gettys and Haller, 2009, 2010Smith et al, 2014), salt stress (e.g., Tootoonchi et al, 2020), and other experimental factors. After visual scoring, a destructive harvest was conducted to collect all live biomass of floating species and all live aboveground shoots of emergent species.…”
Section: Methodsmentioning
confidence: 99%
“…This goal is most often achieved by using herbicides that have been approved by the U.S. Environmental Protection Agency (USEPA) for use in aquatic systems, with statewide oversight and coordination of treatments provided by the Florida Fish and Wildlife Conservation Commission (FWC, 2018(FWC, , 2019a. For example, the FWC oversaw the expenditure of $17.007 million and $15.126 million in federal and state funds to control aquatic plants in Florida's public water bodies in fiscal year (FY) 2017-18 and FY 2018-19, respectively (FWC, 2018. More than half of this funding ($10.01 million and$8.86 million in FY 2017-18 andFY 2018-19, respectively) was allocated for managing the submersed weed hydrilla (Hydrilla verticillata), whereas %25% of those monies ($4.04 million in FY 2017-18 and$4.19 million in FY 2018-19) was spent for floating plant control, which primarily comprise waterhyacinth (Eichhornia crassipes) and waterlettuce (Pistia stratiotes).…”
mentioning
confidence: 99%
See 1 more Smart Citation